Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.